The Influence of Financial Technology, Digital Payment Systems, Financial Inclusion, and Government Financial Support on the Sustainable Financial Performance of MSMEs in Surakarta District - Tiffani Razifadila; Fatchan Achyani (Danadyaksa: Post Modern Economy Journal, 2026)
The rapid development of digital finance has created new opportunities for Micro, Small, and Medium-Sized Enterprises (MSMEs) to improve sustainable financial performance through technological adoption, financial accessibility, and institutional support. This study aims to examine the influence of Financial Technology, Digital Payment Systems, Financial Inclusion, and Government Financial Support on the sustainable financial performance of MSMEs in Surakarta District. This research employed a quantitative approach using primary data collected through structured questionnaires distributed to MSME owners. The sample was selected using purposive sampling based on specific criteria, including business operation duration, digital financial service utilization, and government support experience. Data were analyzed using IBM SPSS Statistics for descriptive analysis and SmartPLS for measurement model evaluation and hypothesis testing through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Financial Technology and Financial Inclusion have a positive and significant effect on MSME sustainable financial performance, while Digital Payment Systems and Government Financial Support do not show significant effects. Simultaneously, all independent variables significantly influence sustainable financial performance. These findings highlight the importance of digital financial adoption and financial accessibility in strengthening MSME sustainability.